Three‐dimensional structure of seminiferous tubules in the adult mouse - Nakata, Hiroki; Wakayama, Tomohiko; Sonomura, Takahiro; Honma, Satoru; Hatta, Toshihisa; Iseki, Shoichi (Journal of anatomy, 2015)
Seminiferous tubules develop from sex cords, which are embryonic structures with simple C‐shaped arches. Histologically, the epithelium of adult mouse seminiferous tubules has been divided into 12 stages based on the associations of spermatogenic cells in four cycles of spermatogenesis. However, the gross characteristics of the seminiferous tubules themselves, including their number, length, run, and mutual relationships remain largely unknown. In the present study, we analyzed all seminiferous tubules in a single adult mouse testis with high resolution using serial paraffin sections and high‐perfomance three‐dimensional reconstruction software. There were 11 seminiferous tubules with an average length of 140 mm. Each tubule ran along circular paths within the testis while making convolutions with cranial and caudal hairpin turns. The cranial turns of all tubules were in contact with the tunica albuginea, whereas the caudal turns were not, resulting in funnel‐shaped networks of these tubules with tapered caudal portions. The caudally located networks surrounded the preceding cranially located networks from the bottom and outside, similar to stacked paper cups. Five out of the 11 seminiferous tubules were continuous from one end to the other both connected with the rete testis (10 connection points). Nine branching points, one blind end, and 18 more connection points with the rete testis were detected in the remaining six seminiferous tubules, making the paths of these tubules complicated to various degrees. The present study revealed that the 3D structures of seminiferous tubules were highly regular as a whole in the adult mouse testis.